Increasing student's creativity by integrating low-cost 3D printing into traditional classroom: a conceptual review - Xu, Wenqin; Md Khambari, Mas Nida (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This paper examines and reviews the relevant articles related to increasing learner creativity through integration of low-cost 3-D printer into traditional classroom’s instruction. Various theories and appropriate instructional strategies are examined as part of the integration process. Armchair analysis technique was conducted in this review with the purpose of generalizing and synthesizing previous studies. The study contributes to the topic by providing an in-depth and comprehensive perspective of the literature related to integration of 3D printing in traditional classroom. There are three sections in this conceptual report. The first section introduced the background of low-cost 3D printing technique and the problems existed in creativity instruction. The second sections reviews the integration of low-cost 3D printing in education and sundry approaches to achieve it. Theories and principles are discussed in the final section of the paper. The findings illustrated that collaborative project-based learning using 3D printer has been adapted by various researchers in multidisciplinary learning situation. Three theories, which includes the condition of learning, constructivism theory, and constructionism theory, are used in different settings to support the learning activities. Shortcomings such as time-consuming, diversity of student technical level, and the defects in low-cost 3D printer products are reported in the literature as well. In sum, the researchers summarize the instructional strategies applied in the integration of 3D printing in the classroom and the theories behind it by using armchair analysis technique.